Photodynamic Inactivation of Endopathogenic Microbiota Using Curcumin- mediated Antimicrobial Photodynamic Therapy - M. Khoobi; Sh. Farkhonde Masoule; M. Pourhajibagher; J. Safari (Journal of Sciences, Islamic Republic of Iran)
Root canal disinfection is one of the main factors governing success of endodontic therapy. Antimicrobial photodynamic therapy (aPDT) is presented as a promising antimicrobial therapy that can eliminate microbiota present in infected root canal systems. In this study, a series of experiments investigated the effects of aPDT on cell viability and biofilm degradation ability of endopathogenic microbiota. Enterococcus faecalis and Pseudomonas aeruginosa strains as the versatile pathogenic microbiota in endodontic infections were used as the tested strains. Curcumin (CUR) and light-emitting diode (LED) were used as the photosensitizer and light source, respectively. The antimicrobial and anti-biofilm effects of CUR-aPDT were assessed by colony forming unit (CFU), and crystal violet assays. CUR-aPDT significantly decreased the CFU/mL count of E. faecalis and P. aeruginosa compared to the control group (P<0.05). The killing percentage of aPDT was achieved 95.0% for E. faecalis and 81.1% for P. aeruginosa. In addition, the biofilm degradation ability of E. faecalis and P. aeruginosa significantly decreased to 41.2% and 30.2%, respectively (P<0.05). According to the results, neither CUR nor LED showed the antimicrobial and anti-biofilm effects when used alone. In conclusion, the results of this study indicated that CUR-aPDT has an appreciable effect on endopathogenic microbiota upon photoactivation.